Boosting Students Critical Thinking in High School: Project- Based Learning on Global Warming - Elsi Oktaviyanti; Dedeh Kurniasih; Dini Hadiarti; Zahratun Nufus (Tarbawi : Jurnal Ilmu Pendidikan, 2024)
The low critical thinking skills in chemistry learning is an issue that requires special attention from teachers. These skills are crucial for preparing a generation capable of competing globally and directly impacting student learning outcomes. This study aims to determine the effect of the project-based learning model on global warming material on the critical thinking skills of high school students. This quantitative study employs a quasi-experimental research design with a one-group pretest-posttest approach. The population of this study consists of 62 students from class X Science at SMAIT AI-Fityan Kubu Raya. Through the purposive sampling technique, class X B, which consists of 33 students, was selected as the sample. Pretest-posttest questions were used as data collection tools to assess students' critical thinking skills and learning outcomes, while observation sheets were used to evaluate student activities during the learning process. Data analysis involved normality tests, homogeneity tests, paired sample T-tests, and n-gain analysis. The results showed that students' critical thinking skills, based on the average pretest score of 46.5, increased to 89.90 in the posttest, with the percentage increase generated by the PjBL model being 92.67%. Therefore, PjBL is very effective as a learning model to improve students' critical thinking skills on global warming.